Reconstructing the world : B.R. Ambedkar and Buddhism in India - Jondhale, Surendra; Jondhale, Surendra; Beltz, Johannes (New Delhi : Oxford University Press, 2004)
Contributed seminar papers.
Keywords: Buddhism -- India -- History -- 20th century -- Congresses; Buddhism and social problems -- India -- Congresses